Potential Effects of Ipomoea reptans Poir. Extract on LDL, HDL levels and liver Histopathology - Kartika Rahma; Frida Octavia Purnomo (Faculty of Medicine, Universitas Diponegoro, 2023)
Background: Ipomoea reptans Poir. extract has been known to have antioxidant, antihypertensive, antidiabetic and anti-obesity activities. The content of the secondary compounds antioxidant in the extract is believed to play an important role in this mechanism also often reported that have regulating cholesterol levels.Objective: This study aims to investigate the antioxidant activity of I. reptans extract on changes in low-density lipoprotein (LDL) and high-density lipoprotein (HDL) and liver histopathology in animal models of hypercholesterolemia that treated with I. reptans extract.Methods: This research was an in vivo experimental study using mice. Twenty five wistar rats were randomly divided into 5 groups: normal group (N), hypercholesterolemic group (Chol), I. reptans extract group at a dose of 200 mg/kg BW, 300 mg/kg BW and 400 mg/kgBB (IE 200; IE 300, and IE 400). In the Chol and IE groups, the rats were induced by cholesterol in the form of a mixture of quail egg yolk and animal oil for 21 days. Then, continued with therapy with I. reptans extract in the IE group only according to their respective doses for 14 days. All rats were then dissected and blood serum taken for analysis of LDL and HDL levels using a colorimetric kit, and liver organs were also taken for histopathological analysis with hematoxylin-Eosin (HE) staining. All research data were analyzed using the Shapiro-Wilk normality test and the Levene's homogeneity test. If the data obtained is normally distributed, it is continued with the One-way Anova comparative test and the LSD post hoc test. If the data obtained is not normally distributed, continue with the Kruskal-Wallis and Mann-Whitney tests.Results: The results showed that the average LDL levels in the N, Chol, IE 200, IE 300 and IE 400 groups were 8.56 ± 1.36, 29.9 ± 1.05, 25.22 ± 4.72, 9.12 ± 0.72, and 9.22 ± 0.77 mg/dL, while the average HDL levels in the were 38.1 ± 2.24, 15.92 ± 4.39, 33.4 ± 5.91, 36.92 ± 0.47, and 42.82 ± 3.27 mg/dL respectively. Liver histopathology in the IE 300 group showed reduced fatty degeneration compared to the Chol group.Conclusion: It can be concluded that the administration of I.reptans extract in hypercholesterolemia rats was able to ameliorates LDL and HDL levels, and improve liver histopathology.